The effects of creatine supplementation on biomechanical, body composition, and performance outcomes in humans: A meta-analysis - Gutiérrez Sancho, Óscar Pablo (2006)
Creatine supplementation has been widely used for athletes and in some studies it has been proved effective; however, there remain some moderator variables that still require meta-analysis. Therefore, the purpose of this study was to conduct such an analysis on the effects of creatine supplementation on biochemical, body composition, and physical performance variables. From a total of 120 experimental studies found in databases, only 55 studies (46 %) were considered appropriate and/or contained the necessary information to obtain effect sizes. Creatine supplementation produced biochemical changes, including increases in excretion parameters. Anthropometric variables, body fat percentage, and lean mass were favorably changed by creatine supplementation. Improved peak power, total work, force power, and a maximal repetition (1RM) were also found following creatine supplementation. There was an evident placebo effect in the variables meta-analyzed; however, there was a clear increase in total work beyond the placebo effect. In summary, creatine supplementation consistently showed positive biochemical, body composition, and power changes in humans.